Percepción social de servicios ecosistémicos en comunidades rurales de la parroquia Guadalupe, provincia de Zamora Chinchipe - Sánchez Carrión, Valeria Paola (2024)
Ecosystem services (ES) are defined as the benefits that people obtain from nature, and have become a fundamental pillar for the subsistence of families. Despite the importance of ES for people, studies on ES have been based on monetary, biophysical factors and how the ecosystem can provide services. For this reason, when natural resource management and conservation projects are established, they tend to fail because the people's perception of the services offered by the environment, as well as their preferences and concerns, are not known. In this context, the present research has the following objectives: a) to evaluate the importance of the ES from a social point of view and, b) to identify the activities that the people of the parish consider relevant to recover the ES. Based on personal surveys conducted with 56 heads of households that carry out their activities in the vicinity of the natural resources of Guadalupe parish, it was found that the most valued ES were related to provisioning and regulating services. The most mentioned activity to recover ES was tree planting, where different exotic and native species stand out: Citrus reticulata, Schizolobium parahybum, Inga spectabilis, among others. In addition, the preferences for supply and cultural ES were influenced by the ethnicity of the heads of household. In conclusion, this study presented a baseline on the importance and perception of ES, and how in the future they can be part of creating effective management plans.